Answers

2015-05-19T14:53:00+05:30
( 57 * 57 * 57 - 37 * 37 * 37 ) / ( 57 * 57 + 37 * 57 + 37 * 37 )=(57³-37³)/(57²+37*57+37²)
let a=57 and b=37
we know the formula a³-b³=(a-b)(a²+ab+b²)
see that the equation is of the same type.
by substituting 57 as a and 37 as b , we get,
=(a³-b³)/(a²+ab+b²)
by applying the above mentioned formula , the equation can be modified as:
=(a+b)(a²+ab+b²)/(a²+ab+b²)
cancelling a²+ab+b² from numerator and denominator, we get:
=(a+b)
since a=57 and b=37 , the answer stands:
57+37
=94.
Ans:The solution of the problem is 94.
1 5 1
Gud answer
...thank u
iT IS WRONG I WROTE A+B IN THE 9TH LINE IT SHOULD BE A-B AND SO THE ANS WILL BE 57-37=20 PLEASE MODIFY IT